Panacea or Mixed Blessing? Learning Goal Orientation Reduces Psychological Detachment via Problem‐Solving Rumination. - Mehmood, Qaiser; Hamstra, Melvyn R. W. (Applied Psychology: An International Review, 2021)
This study seeks to test whether employee learning goal orientation, due to its prompting of work goal‐related thoughts at home (problem‐solving rumination), is associated with lower detachment from work during non‐work time (and higher work creativity). For learning goal‐oriented employees, the goal to achieve work‐related improvements is chronically cognitively accessible. Moreover, highly accessible work goals could become more frequently activated at home when cues about work tasks permeate the boundaries of the home role. Accordingly, we further hypothesized that the link between learning goal orientation and problem‐solving rumination (and indirectly detachment and creativity) is stronger for individuals with weaker "role segmentation." A time‐lagged study among 300 employees supported our predictions: learning goal orientation, via problem‐solving rumination, predicted psychological detachment (and creativity), and these direct and indirect relationships were stronger when role segmentation was weaker. The results of this study imply that those highly motivated and strongly contributing LGO employees may also be most vulnerable and may benefit from proper boundary management.